ANALYSIS OF THE ROLE OF TIKTOK VISUAL CONTENT IN SHAPING GENERATION Z'S VISITING INTERESTS TO BUKIT CENDANA PESAWARAN, LAMPUNG PROVINCE - Riska Puja Ananda; Yunada Arpan; Sri Suyarti (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the influence of TikTok content on Generation Z's interest in visiting Bukit Cendana, Pesawaran, Lampung Province. Using a descriptive quantitative approach, data were collected through questionnaires distributed to 100 respondents with purposive sampling. Data analysis included validity, reliability, classical assumptions, simple linear regression, and hypothesis testing using IBM SPSS Statistics 26. The results showed that TikTok content had a significant influence on interest in visiting with a coefficient of determination of 71.3%. The regression equation Y = 7.521 + 0.615X indicates that every one unit increase in TikTok content contributes to an increase in interest in visiting by 0.615 units. The t-test showed a significance of 0.000 (p <0.05) with a t-count of 10.617> t-table 1.984, so the hypothesis was accepted. In conclusion, TikTok visual content is effective in shaping Generation Z's interest in visiting Bukit Cendana. Tourism managers are advised to optimize TikTok as a promotional medium.